2008
DOI: 10.1007/s10535-008-0075-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tea cytosolic glutamine synthetase is tissue specific and induced by cadmium and salt stress

Abstract: Glutamine synthetase (GS) showed highest expression and activity in bud (youngest topmost leaf) of Camellia sinensis, lower in older leaves, while lowest activity in stem and roots. GS expression and activity was increased by ammonium and nitrate and also by cadmium and salt stress but decreased by copper, aluminum, drought, cold and heat stress.Additional key words: abiotic stress, Camellia sinensis, metal stress, N-source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Their study provides a basis for studying the drought tolerance mechanism of the tea plant, which will also be a valuable resource for the functional genomics study of woody plants in future. Rana et al (2008) reported that expression of tea cytosolic glutamine synthetase in tissue specific glutamine synthetase transcript by both salinity and Cd indicates that abiotic stress can induce the expression of this gene; thus, it contains stress responsive elements in its promoter region. Glutamine synthetase is an enzyme that plays an important role in nitrogen assimilation, growth, and development of plants.…”
Section: Molecular Physiology Of Abiotic Stress Responses In Teamentioning
confidence: 99%
“…Their study provides a basis for studying the drought tolerance mechanism of the tea plant, which will also be a valuable resource for the functional genomics study of woody plants in future. Rana et al (2008) reported that expression of tea cytosolic glutamine synthetase in tissue specific glutamine synthetase transcript by both salinity and Cd indicates that abiotic stress can induce the expression of this gene; thus, it contains stress responsive elements in its promoter region. Glutamine synthetase is an enzyme that plays an important role in nitrogen assimilation, growth, and development of plants.…”
Section: Molecular Physiology Of Abiotic Stress Responses In Teamentioning
confidence: 99%
“…Glutamine synthetase (GS, A3) catalyzes the formation of glutamate, which is an important component of reduced glutathione and phytochelatins (PCs). Rana et al (2008) observed that the expression of cytosolic GS was induced by Cd and salt stress. Studies have found that beta-tubulin and alpha-1,4-glucan-protein synthase are involved in plant cell wall metabolism (SPOKEVICIUS et al, 2007;JIN et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The reverse Northern dot-blot analysis showed an increase of this transcript after 3 days of Cd treatment. Glutamine synthetase plays a role in the flow of nitrogen into nitrogenous organic compounds by catalyzing the assimilation of ammonia into glutamine, which is then converted to glutamate via the action of glutamate synthase (Li et al 1993;Rana et al 2008). Glutamine regulates the cellular redox balance, including oxidative metabolism, apoptosis, and cell proliferation in mammalian cells (Matés et al 2002).…”
Section: Discussionmentioning
confidence: 99%